Odpowiedzi

Najlepsza Odpowiedź!
2010-03-07T12:28:19+01:00
3-(3x/2)=(5/8)-[(4x-3)/6](*24)
24*3-24*(3x/2)=24(5/8)-24[(4x-3)/6]
72-36x=15-4[4x-3]=
72-36x=15-16x+12
-36x+16x=15+12-72
-20x=-45
x=2i1/4

spr.
3-(3x/2)=(5/8)-[(4x-3)/6](*24)
24*3-24*(3*9/4)/2=24(5/8)-24[(4*9/4-3)/6]=
72-12(27/4)=15-4[9-3]=
72-81=15-36+12
-9=-9


1-{([x-2]/4)+(2/3)}=x(*12)
12*1-{(12[x-2]/4)+12(2/3)}=12x
12-[3x-6]+8]=12x
12-3x+6-8=12x
-3x-12x=8-12-6
-15x=-10
x=2/3

spr.
1-{([x-2]/4)+(2/3)}=x(*12)
12*1-{(12[2/3-2]/4)+12(2/3)}=12*2/3
12-[3[2/3-2]+8]=8
12-[2-6+8]=8
12-2+6-8=8
8=8